PERAN PANDEMI COVID-19 PADA PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN INDUSTRI DASAR DAN KIMIA - Abdillah, Cahaya; Yahya, Muchlis; Rahmiyanti, Firdha (AKUNTANSI DEWANTARA, 2024)
This study aims to examine the influence of the Covid-19 pandemic (measured by the number of laid-off employees) on moderating the relationship between Return on Asset (ROA) and Asset Size with Price Book Value (PBV) as the dependent variable. The study focuses on manufacturing companies within the basic and chemical industry sectors listed on the Indonesia Stock Exchange during the 2020 period. Out of a population of 83, 55 samples were selected using purposive sampling. This research employs quantitative methods and data sourced from www.idx.co.id. Moderated Regression Analysis (MRA) is used as the analytical tool. The research issue arose in 2020 with the emergence of the Covid-19 pandemic, which had a negative impact on the economy, as evidenced by a decline in PBV across nine manufacturing sectors listed on the Indonesia Stock Exchange. Among these sectors, only the basic and chemical industry sector experienced a strengthening of PBV, with the decline in 2020 being smaller compared to 2019. The research findings indicate that the Covid-19 variable insignificantly weakens the positive relationship between ROA and PBV. Meanwhile, the positive relationship between Asset Size and PBV can be significantly weakened by the Covid-19 variable.